2009
DOI: 10.1002/anie.200901266
|View full text |Cite
|
Sign up to set email alerts
|

A Color‐Tunable Europium Complex Emitting Three Primary Colors and White Light

Abstract: Tunable emission colors are shown by a single‐component emitter incorporating an EuIII moiety as the origin of red light and an organic ligand comprising coumarin (blue emission) and Rhodamine 6G (green emission) fluorophores. This dye can emit three individual primary colors (blue, green, and red) as well as nearly pure white light (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
124
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(126 citation statements)
references
References 47 publications
(13 reference statements)
2
124
0
Order By: Relevance
“…The PL spectra for 8 in the thin lm showed red shis from their PL in solution. Similar results were obtained for compounds [11][12][13][14][15][16][17][18]. Such a kind of red shi in PL emission in the solid state is common and has been observed by others for organic small molecules as well as polymeric materials 33 possibly due to (a) the exciton hopping process in the solid state, (b) the intermolecular interaction in the solid state i.e.…”
supporting
confidence: 85%
“…The PL spectra for 8 in the thin lm showed red shis from their PL in solution. Similar results were obtained for compounds [11][12][13][14][15][16][17][18]. Such a kind of red shi in PL emission in the solid state is common and has been observed by others for organic small molecules as well as polymeric materials 33 possibly due to (a) the exciton hopping process in the solid state, (b) the intermolecular interaction in the solid state i.e.…”
supporting
confidence: 85%
“…Many of such single-component full-color-emitting phosphors have emerge very recently, ranging from semiconducting nanocrystals [1,2], organic compound [3], complex [4,5], hybrid [6] to rare earth doped inorganic hosts [7][8][9][10][11][12][13][14][15][16][17][18][19][20] as well. As to the present interest in a full-color phosphor, A 3 MgSi 2 O 8 :Eu 2+ , Mn 2+ (A = Ba, Sr, Ca) [21], we have identified that, a green-band-emission peaked at ∼505 nm does not originate from Ba sites in Ba 3 MgSi 2 O 8 host lattice but from those in a newly formed orthosilicate phase, Ba 2 SiO 4 [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Recently, researchers have focused on color-tunable luminescent materials based on polymer materials. [7][8][9][10][11] The common method to create such materials is using multiple chromophores to modify polymeric backbone. [12][13][14][15] However, this method is limited because dialing color requires the occurrence of reaction between polymer and chromophore monomer.…”
Section: Introductionmentioning
confidence: 99%